Normothermic regional perfusion for donation after circulatory death donors. Issue 2 (17th April 2023) - Pasrija, Chetan; Tipograf, Yuliya; Shah, Ashish S.; Trahanas, John M.
Abstract : Purpose of review: This review is intended to provide an update on the logistics, technique, and outcomes associated with normothermic regional perfusion (NRP), as well as provide a discussion of the associated ethical issues. Recent findings: There has been renewed interest in utilizing NRP to increase quality and availability of organs from donation after circulatory death (DCD) donors. Our institution has increasing experience with thoraco-abdominal NRP (TA-NRP) in controlled DCD donors (cDCD), whereas abdominal NRP (A-NRP) has been used with success in both cDCD and uncontrolled DCD (uDCD). There is increasing evidence that NRP can be conducted in a practical and cost-efficient manner, and that the organ yield may be of better quality than standard direct procurement and perfusion (DPP). Summary: NRP is increasingly successful and will likely prove to be a superior method for cDCD recovery. However, before TA-NRP can be widely accepted the ethical debate surrounding this technique must be settled. Video abstract: http://links.lww.com/COOT/A11